Brief of Amicus Curiae 290 Criminal Law and Mental Health Law Professors in Support of Petitioner's Request for Reversal and Remand, Kahler v. Kansas, 18-6135 (U.S. June 6, 2019) - Rothstein, Paul F (2019)
Amici curiae are a group of philosophically and politically diverse law school professors and scholars in the fields of criminal law and mental health from a variety of disciplines who have been teaching and writing about the insanity defense and related issues throughout their careers. They include the authors of leading criminal law and mental health law treatises and casebooks and numerous important scholarly books and articles. Amici believe this case raises important questions about principles of criminal responsibility, the integral role of the insanity defense in Anglo-American law, and the inadequacy of the “mens rea alternative” to the traditional affirmative defense. Their teaching and research on the subject have given them a unique appreciation of the historical and doctrinal significance of the defense of legal insanity